2020
DOI: 10.1038/s41598-020-70311-8
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans possess a general program to enter cryptobiosis that allows dauer larvae to survive different kinds of abiotic stress

Abstract: All organisms encounter abiotic stress but only certain organisms are able to cope with extreme conditions and enter into cryptobiosis (hidden life). Previously, we have shown that C. elegans dauer larvae can survive severe desiccation (anhydrobiosis), a specific form of cryptobiosis. Entry into anhydrobiosis is preceded by activation of a set of biochemical pathways by exposure to mild desiccation. This process called preconditioning induces elevation of trehalose, intrinsically disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 39 publications
(40 reference statements)
2
34
0
Order By: Relevance
“…In a daf-2(e1370) background, we confirmed that both lea-1Δ and lea-1(tm6452) dauer worms were sensitive to desiccation at high relative humidity (97.5%) and at a more stringent desiccation stress of 60% humidity (Fig. 2A), consistent with published results [10, 29, 30]. Additionally, dauer worms of each of these mutant strains were sensitive to osmotic stress in a concentrated salt solution.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In a daf-2(e1370) background, we confirmed that both lea-1Δ and lea-1(tm6452) dauer worms were sensitive to desiccation at high relative humidity (97.5%) and at a more stringent desiccation stress of 60% humidity (Fig. 2A), consistent with published results [10, 29, 30]. Additionally, dauer worms of each of these mutant strains were sensitive to osmotic stress in a concentrated salt solution.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have relied on RNAi for gene knockdown and did not fully eliminate lea-1 mRNA [10] or noted that RNAi seldom fully eliminates the target mRNA [29]. One recent study used a deletion allele, but only confirmed the phenotype of desiccation sensitivity [30]. Furthermore, there are many isoforms of LEA-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when encountering a harsh environment, overcrowding or food scarcity, C. elegans pauses the reproductive cycle and enters diapause by forming a non-feeding dauer larva (6). It has been shown that this dauer larva can survive severe desiccation (5), high osmotic pressure, or freezing (7). The dauer larvae differ from reproductive larvae in both metabolism and morphology (6,8).…”
Section: Introductionmentioning
confidence: 99%